An organic solar cell and a heterogeneous interface control method thereof
By using ethoxy long-chain organic phosphoric acid in organic solar cells to passivate metal oxide nanoparticles and perform interface regulation, the interfacial recombination problem of molybdenum oxide nanoparticles in organic solar cells is solved, and the photoelectric conversion efficiency and stability are improved.
Patent Information
- Application Number
- CN202411490049.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In existing organic solar cells, metal oxide nanoparticles such as molybdenum oxide (MoOx) nanoparticles have a large number of surface interface defect states, which do not match the energy level of high-performance non-fullerene receptors, resulting in serious recombination of carriers at the interface, reducing the effective separation and migration efficiency of photogenerated charges, and affecting the efficiency and stability of organic solar cells.
By blending ethoxy long-chain organic phosphoric acid with metal oxide nanoparticles and stirring with an ultrasonic oscillator, the metal oxide nanoparticles are passivated to form a nanosolution. Then, the nanosolution is spin-coated on the indium tin oxide surface of the organic solar cell and undergoing low-temperature annealing treatment to regulate the interface environment between the metal oxide nanoparticles and the organic semiconductor material.
The chemical, electrical and electronic characteristics of the organic-inorganic heterointerface are improved, the photogenerated charge separation and transfer efficiency of semiconductor materials are improved, and the photoelectric conversion efficiency and photostability of organic solar cells are improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to an organic solar cell and a heterogeneous interface control method thereof. Background Art
[0002] As a sustainable and clean energy, solar energy plays an important role in solving the global energy crisis. Photocatalytic technology is an important means of converting solar energy into chemical energy using semiconductor materials. When semiconductor materials absorb sunlight, the electrons in their valence band will be excited to jump to the conduction band, generating photogenerated electron-hole pairs, which in turn drive chemical reactions.
[0003] In recent years, organic solar cells have attracted extensive attention due to their advantages such as light weight, flexibility and ease of large-scale manufacturing. At present, the photoelectric conversion efficiency of organic solar cells is close to 19%, showing great application potential. However, metal oxide nanoparticles such as molybdenum oxide (MoOx) nanoparticles have a large number of surface interface defect states, which do not match the energy levels of high-performance non-fullerene acceptors, which leads to serious recombination of carriers at the interface, reducing the effective separation and migration efficiency of photogenerated charges, resulting in poor utilization of photogenerated charges and low photo-chemical energy conversion efficiency. In addition, MoOx nanoparticles are prone to agglomeration in solution, which not only affects the processing performance of the material, but also limits its conductivity. These problems seriously restrict the charge transport between the organic active layer and the metal oxide nanoparticles, thereby affecting the efficiency and stability of organic solar cells.
[0004] Therefore, it is crucial to develop passivated metal oxide nanoparticle materials with excellent properties and to regulate the microenvironment at the interface between metal nanoparticles and semiconductor materials to achieve efficient charge separation and transfer, thereby obtaining efficient photocatalytic performance, in order to realize low-cost and high-performance organic solar cells. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an organic solar cell and a heterogeneous interface control method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for regulating a heterogeneous interface of an organic solar cell comprises the following steps:
[0008] S1: mixing ethoxylated long-chain organic phosphoric acid and metal oxide nanoparticles in an organic solvent to obtain a basic solution;
[0009] S2: stirring the base solution using an ultrasonic oscillator to passivate the metal oxide nanoparticles to obtain a nano solution;
[0010] S3: spin coating the nano-solution on the surface of indium tin oxide of the organic solar cell to obtain a thin film;
[0011] S4: The film is subjected to low temperature annealing treatment to achieve interface regulation between metal oxide nanoparticles and organic semiconductor materials.
[0012] As a preferred technical solution of the present invention, the ethoxy long-chain organic phosphoric acid is one of [4-(3,6-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid, [4-(2,7-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid, [4-(2-(2-methoxyethoxy)ethoxy)benzyl]phosphonic acid, [4-(2-methoxyethoxy)benzyl]phosphonic acid molecules, and their structural formulas are as follows:
[0013] .
[0014] As a preferred technical solution of the present invention, in S1, the mass feed ratio of ethoxy long-chain organic phosphoric acid to metal oxide nanoparticles is 1:5-20, in S2, the passivation reaction time is 6-24h, and the concentration of metal oxide nanoparticles in the nano solution is 1-100mg·mL -1 .
[0015] As a preferred technical solution of the present invention, in S1, the organic solvent is one of an alcohol solvent, a halogen-containing solvent, and a non-halogen solvent.
[0016] As a preferred technical solution of the present invention, in S4, the low-temperature annealing treatment temperature is 20-200° C., and the annealing time is 5-30 min.
[0017] As a preferred technical solution of the present invention, the metal oxide nanoparticles are molybdenum oxide nanoparticles;
[0018] The steps of preparing the molybdenum oxide nanoparticles are as follows:
[0019] SS1: adding deionized water to molybdenum trioxide powder to obtain a suspension;
[0020] SS2: adding hydrogen peroxide to the suspension to obtain a mixed solution;
[0021] SS3: heating the mixed solution at a temperature of 30-60°C, stirring the mixed solution with an ultrasonic oscillator, and reacting for 3-5 hours to obtain a pre-treated solution;
[0022] SS4: naturally cooling the pretreated liquid to room temperature, filtering the pretreated liquid, filtering out and recovering solid particles to obtain a filtrate;
[0023] SS5: The filtrate is concentrated to obtain molybdenum oxide nanoparticles.
[0024] As a preferred technical solution of the present invention, in the step of preparing molybdenum oxide nanoparticles, per 1g of molybdenum trioxide powder:
[0025] The content of deionized water is 50-100mL;
[0026] The mass concentration of hydrogen peroxide is 30%, and the content is 5-10mL.
[0027] An organic solar cell comprises a substrate, indium tin oxide, a hole transport layer, an active layer, an electron transport layer and a metal electrode layer which are arranged in layers from bottom to top;
[0028] The hole transport layer is prepared by adopting the above-mentioned heterogeneous interface regulation method for an organic solar cell.
[0029] As a preferred technical solution of the present invention, the active layer is a blended film of an organic electron donor material and an organic electron acceptor material;
[0030] The organic electron donor material is PM6;
[0031] The organic electron acceptor material is one of Y6, B0-4Cl, B0-4Cl and Y6-10 combination materials.
[0032] As a preferred technical solution of the present invention, the substrate material is one of glass, quartz, flexible polyethylene terephthalate, and flexible polyethylene naphthalate.
[0033] The present invention has the following beneficial effects:
[0034] By passivating metal oxide nanoparticles with ethoxy long-chain organic phosphoric acid, the chemical, electrical and electronic properties of the organic-inorganic heterointerface are improved. By using organic phosphoric acid to passivate molybdenum oxide nanoparticles, the micro-environment of the interface between metal nanoparticles and organic semiconductor materials is regulated, the efficiency of photogenerated charge separation and transfer of semiconductor materials is improved, and the highest photoelectric conversion efficiency of organic solar cells using metal oxides as hole transport layers is achieved, which improves the photostability of organic solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of the structure of an organic solar cell proposed by the present invention;
[0036] Figure 2 is the particle size distribution diagram of the MoOx nano solution in Examples 1-4;
[0037] Figure 3The morphology of different hole transport layers prepared from MoOx nano-solutions in Examples 1-4;
[0038] Figure 4 The current density-voltage curve of the solar cell device prepared by the MoOx nano solution in Examples 1-4. DETAILED DESCRIPTION
[0039] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other. The reagents used in each embodiment can be commercially available products without special restrictions.
[0040] A method for regulating a heterogeneous interface of an organic solar cell, comprising:
[0041] The method comprises mixing an ethoxylated long-chain organic phosphoric acid and metal oxide nanoparticles in an organic solvent to obtain a basic solution, fully stirring the basic solution with a magnetic stirrer or an ultrasonic oscillator, passivating the metal oxide nanoparticles with ethoxylated long-chain organic phosphoric acid molecules, and obtaining a clear nano solution. In the process of preparing an organic solar cell, the nano solution is spin-coated on the surface of indium tin oxide of the organic solar cell, and the spin-coated film is annealed at low temperature to prepare a hole transport layer. The hole transport layer is introduced into the organic solar cell, thereby achieving high efficiency of the organic solar cell and improving photostability.
[0042] Among them, the ethoxy long-chain organic phosphoric acid molecule is one of [4-(2-(2-methoxyethoxy)ethoxy)benzyl]phosphonic acid, [4-(2-methoxyethoxy)benzyl]phosphonic acid, [4-(3,6-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid, and [4-(2,7-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid. These phosphonic acid molecules are sequentially recorded as PB1, PB2, PB3 and PB4, and their structural formulas are shown below:
[0043] ;
[0044] In S1, the mass feed ratio of ethoxy long-chain organic phosphoric acid to metal oxide nanoparticles is 1:5-20, and the organic solvent is one of an alcohol solvent, a halogen-containing solvent, and a non-halogen solvent; in S2, the passivation reaction time is 6-24h, and the concentration of metal oxide nanoparticles in the nanosolution is 1-100mg·mL -1 ; In S4, the low temperature annealing temperature is 20-200°C, and the annealing time is 5-30 min;
[0045] Wherein, the metal oxide nanoparticles are molybdenum oxide nanoparticles;
[0046] The preparation steps of molybdenum oxide nanoparticles are as follows:
[0047] SS1: Add deionized water to molybdenum trioxide powder to obtain a suspension, wherein the content of deionized water is 50-100 mL per 1 g of molybdenum trioxide powder;
[0048] SS2: Add hydrogen peroxide (H2O2) with a mass concentration of 30% to the suspension to obtain a mixed solution, and the content of hydrogen peroxide is 5-10mL per 1g of molybdenum trioxide powder;
[0049] SS3: heating the mixed solution at a temperature of 30-60°C, stirring the mixed solution with an ultrasonic oscillator, and the reaction time is 3-5h to obtain a pre-treated solution;
[0050] SS4: naturally cooling the pretreated liquid to room temperature, filtering the pretreated liquid, filtering out and recovering solid particles to obtain a filtrate;
[0051] SS5: The filtrate is concentrated to obtain molybdenum oxide nanoparticles. Example 1
[0052] In this embodiment, a PB1-MoOx nanoparticle was prepared according to the above-mentioned steps for preparing molybdenum oxide nanoparticles. The specific preparation method is as follows:
[0053] Add 10 g of molybdenum trioxide powder, 200 mL of deionized water, and 50 mL of 30% H2O2 into a 500 mL flask, heat to 50 °C, and ultrasonically oscillate for 3 h. Filter out the unreacted insoluble matter, collect the filtrate, and concentrate to obtain 8.9 g of golden yellow powder, recorded as MoOx NPs.
[0054] Add 100 mg of MoOx NPs, 10 mg of ethoxylated long-chain organic phosphoric acid PB1, and 20 mL of ethylene glycol monomethyl ether into a 30 ml flask, stir to completely dissolve, let stand for 24 h, and filter with a filter membrane to obtain a passivated PB1-MoOx nanosolution. Example 2
[0055] In this embodiment, a PB2-MoOx nanoparticle is prepared according to the above-mentioned steps for preparing molybdenum oxide nanoparticles. The specific preparation method is as follows:
[0056] Add 10 g of molybdenum trioxide, 200 mL of deionized water, and 50 mL of 30% H2O2 into a 500 mL flask, heat to 50 °C, and ultrasonically oscillate for 3 h. Filter out the unreacted insoluble matter, collect the filtrate, and concentrate to obtain 8.9 g of golden yellow powder, recorded as MoOx NPs.
[0057] Add 100 mg of MoOx NPs, 10 mg of ethoxylated long-chain organic phosphoric acid PB2, and 20 mL of ethylene glycol monomethyl ether into a 30 ml flask, stir to completely dissolve, let stand for 24 h, and filter with a filter membrane to obtain a passivated PB2-MoOx nanosolution. Example 3
[0058] In this embodiment, a PB3-MoOx nanoparticle is prepared according to the above-mentioned steps for preparing molybdenum oxide nanoparticles. The specific preparation method is as follows:
[0059] Add 10 g of molybdenum trioxide, 200 mL of deionized water, and 50 mL of 30% H2O2 into a 500 mL flask, heat to 50 °C, and ultrasonically oscillate for 3 h. Filter out the unreacted insoluble matter, collect the filtrate, and concentrate to obtain 8.9 g of golden yellow powder, recorded as MoOx NPs.
[0060] Add 100 mg of MoOx NPs, 10 mg of ethoxylated long-chain organic phosphoric acid PB3, and 20 mL of ethylene glycol monomethyl ether into a 30 ml flask, stir to completely dissolve, let stand for 24 h, filter with a filter membrane, and obtain a passivated PB3-MoOx nano solution. Example 4
[0061] In this embodiment, a PB4-MoOx nanoparticle is prepared according to the above-mentioned steps for preparing molybdenum oxide nanoparticles. The specific preparation method is as follows:
[0062] Add 10 g of molybdenum trioxide, 200 mL of deionized water, and 50 mL of 30% H2O2 into a 500 mL flask, heat to 50 °C, and ultrasonically oscillate for 3 h. Filter out a small amount of insoluble matter, collect the filtrate, and concentrate to obtain 8.9 g of golden yellow powder, recorded as MoOx NPs.
[0063] Add 100 mg of MoOx NPs, 10 mg of ethoxylated long-chain organic phosphoric acid PB4, and 20 mL of ethylene glycol monomethyl ether into a 30 ml flask, stir to completely dissolve, let stand for 24 h, filter with a filter membrane, and obtain a passivated PB4-MoOx nano solution.
[0064] Reference Figure 1 , an organic solar cell, comprising a substrate, indium tin oxide, a hole transport layer, an active layer, an electron transport layer and a metal electrode layer arranged in layers from bottom to top, and the preparation process of the organic solar cell is as follows:
[0065] Treatment of substrate and indium tin oxide (ITO): The transparent conductive glass with strips of indium tin oxide (ITO) etched on the surface was cleaned with detergent, deionized water, acetone and isopropanol ultrasonic oscillation for 30 minutes, dried with nitrogen flow, and then treated with ultraviolet and ozone plasma for 10 minutes;
[0066] Preparation of hole transport layers (HTLs): The prepared nano-solution was spin-coated on the ITO surface at 4500 rpm and annealed at 170 °C for 20 min to obtain the HTLs layer, which was then transferred to a glove box;
[0067] Preparation of active layers: annealing at 100 °C for 7 min in a glove box; when the active layer is PM6:BTP-eC9, the solution is 16.5 mg mL -1 The chloroform solution was prepared with a donor-acceptor weight ratio of 1:1.2, the additive was 0.25% DIO, the solution was spin-coated at a speed of 3000 rpm, and the film was annealed at 90 °C for 7 min.
[0068] Preparation of electron transport layers (ETLs): 1 mg mL -1 The PDINN methanol solution was spin-coated on the active layer at a rotation speed of 3800 rpm to obtain PDINNETLs;
[0069] Preparation of cathode electrode: at 2.0×10 -4 The Ag electrode with a thickness of 100 nm was deposited by thermal evaporation at a background pressure of 2.0 Pa.
[0070] In addition, the substrate material can also be one of quartz, flexible polyethylene terephthalate, and flexible polyethylene naphthalate; the active layer is a blended film of an organic electron donor material and an organic electron acceptor material, the organic electron donor material is PM6, and the organic electron acceptor material is one of a combination of Y6, B0-4Cl, B0-4Cl and Y6-10.
[0071] According to the above-mentioned preparation process of the organic solar cell, four organic solar cells are prepared, and the nano solutions used for the hole transport layers in the four organic solar cells are: the PB1-MoOx nano solution in Example 1, the PB2-MoOx nano solution in Example 2, the PB3-MoOx nano solution in Example 3, and the PB4-MoOx nano solution in Example 4;
[0072] At a light intensity of 100 mW / cm 2 Under the AM 1.5G simulated sunlight, the particle size distribution of the MoOx nano-solutions in Examples 1-4 is as follows Figure 2 As shown, the peak of the curve in the figure corresponds to the most common particle size in the solution, among which the most common particle size in PB3-MoOx is the largest, and the most common particle size in PB2-MoOx is the smallest; further, the morphologies of different hole transport layers prepared from the MoOx nano solutions in Examples 1-4 are as follows Figure 3As shown, the hole transport layer corresponding to PB3-MoOx has a rough surface, large gaps, the most serious surface defects, and the lowest corresponding photoelectric conversion efficiency; the hole transport layer prepared by PB2-MoOx has a smooth morphology, the smallest surface defects, and the highest corresponding photoelectric conversion efficiency;
[0073] Furthermore, the current density-voltage curves of the solar cell devices prepared by the four hole transport layers are as follows: Figure 4 As shown; the performance parameter measurement results of the above four solar cell devices are as follows:
[0074]
[0075] Table 1 (Device parameter table based on different MoOx in Examples 1-4)
[0076] In Table 1, Voc represents open circuit voltage, which refers to the maximum voltage that a solar cell can generate when there is no external load. A high Voc may cause other parameters to decrease, so it needs to be considered together with other parameters when evaluating device performance; Jsc represents short circuit current density. A higher Jsc indicates that the battery can generate a larger current under standard conditions. Similarly, Jsc needs to be considered together with other parameters to evaluate the overall performance of the battery; FF represents fill factor, which measures the degree of closeness between the actual efficiency of a solar cell when converting light energy into electrical energy and the theoretical maximum efficiency; PCE represents photoelectric conversion efficiency, which is an extremely important indicator for measuring the performance of solar cells and directly affects the practicality and economy of solar cells;
[0077] According to the above test results, the open circuit voltage of the organic solar cell device based on PB2-MoOx is 0.878V, which is higher than the open circuit voltage values of the other three devices, and its short circuit current density is 26.45mA·cm -2 , slightly lower than the measured value of the PB4-MoOx device, its filling factor is 0.81, which is greater than the filling factor values of the other three devices, and its photoelectric energy conversion efficiency is 18.84%, which is also greater than the measured values of the other three devices. Comprehensive evaluation shows that the overall performance of the PB2-MoOx-based device is better than that of the other three devices;
[0078] It can be seen that this heterogeneous interface regulation method can be applied to the preparation of thin-film solar cell devices or components, which can effectively adjust the interface contact between metal nanoparticles and organic semiconductor materials and improve the efficiency of photogenerated charge separation and transfer of semiconductor materials.
[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for regulating heterogeneous interfaces of organic solar cells, characterized in that: The following steps are involved: S1: mixing ethoxylated long-chain organic phosphoric acid and metal oxide nanoparticles in an organic solvent to obtain a basic solution; S2: stirring the base solution using an ultrasonic oscillator to passivate the metal oxide nanoparticles to obtain a nano solution; S3: spin coating the nano-solution on the surface of indium tin oxide of the organic solar cell to obtain a thin film; S4: subjecting the film to low temperature annealing treatment to achieve interface regulation between metal oxide nanoparticles and organic semiconductor materials; The ethoxy long-chain organic phosphoric acid is one of [4-(3,6-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid, [4-(2,7-bis(2-methoxyethoxy)9-H-carbazole-9-yl)butyl]phosphonic acid, [4-(2-(2-methoxyethoxy)ethoxy)benzyl]phosphonic acid, and [4-(2-methoxyethoxy)benzyl]phosphonic acid molecules, and their structural formulas are as follows: 。 2. The method for controlling heterogeneous interfaces of organic solar cells according to claim 1, characterized in that: In S1, the mass feed ratio of ethoxy long-chain organic phosphoric acid to metal oxide nanoparticles is 1:5-20, in S2, the passivation reaction time is 6-24h, and the concentration of metal oxide nanoparticles in the nano solution is 1-100 mg·mL -1 .
3. The method for controlling heterogeneous interfaces of organic solar cells according to claim 1, characterized in that: In the above S1, the organic solvent is one of an alcohol solvent, a halogen-containing solvent, and a non-halogen solvent.
4. The method for controlling heterogeneous interfaces of organic solar cells according to claim 1, characterized in that: In the step S4, the low temperature annealing treatment temperature is 20-200° C., and the annealing time is 5-30 min.
5. The method for controlling heterogeneous interfaces of organic solar cells according to claim 1, characterized in that: The metal oxide nanoparticles are molybdenum oxide nanoparticles; The steps of preparing the molybdenum oxide nanoparticles are as follows: SS1: adding deionized water to molybdenum trioxide powder to obtain a suspension; SS2: adding hydrogen peroxide to the suspension to obtain a mixed solution; SS3: heating the mixed solution at a temperature of 30-60°C, stirring the mixed solution with an ultrasonic oscillator, and the reaction time is 3-5h to obtain a pre-treated solution; SS4: naturally cooling the pretreated liquid to room temperature, filtering the pretreated liquid, filtering out and recovering solid particles to obtain a filtrate; SS5: The filtrate is concentrated to obtain molybdenum oxide nanoparticles.
6. The method for controlling the heterogeneous interface of an organic solar cell according to claim 5, characterized in that: In the step of preparing molybdenum oxide nanoparticles, per 1g of molybdenum trioxide powder: The content of deionized water is 50-100mL; The mass concentration of hydrogen peroxide is 30%, and the content is 5-10mL.
Citation Information
Patent Citations
Organic solar cell and organic-inorganic heterogeneous interface regulation and control method thereof
CN113903864A
Metal oxide paste composition and preparaton method of a semiconductor electrode using the same
KR1020110128264A